(untitled) (Bangladesh Journal of Medical Science, 2026)
Psychological distress remains underdiagnosed in oncology settings across Low- and Middle-Income Countries, where transcultural validation of screening instruments and identification of treatment-specific predictors are critical for integrated psychosocial care. This cross-sectional study aimed to validate the Hospital Anxiety and Depression Scale (HADS) in a Moroccan oncological population and to examine the differential associations of anxiety and depression with sociodemographic, clinical, and treatmentrelated variables. Conducted at the Institut National d’Oncologie in Rabat, the study enrolled a consecutive non-probability sample of adult patients aged 18 to 60 years with histologically confirmed cancer. Psychological distress was assessed using the 14-item HADS, and the psychometric structure was explored via principal component analysis with Varimax rotation, while internal consistency was evaluated using Cronbach’s alpha; bivariate associations were examined through Spearman’s rank correlation, and multivariate associations with treatment type were modeled via multiple linear regression. The HADS demonstrated excellent sampling adequacy (Kaiser-Meyer-Olkin = 0.897) and a significant Bartlett’s test of sphericity (χ² = 725.68, p < 0.001), with principal component analysis confirming a robust two-factor structure accounting for 58.06% of total variance and excellent internal consistency (Cronbach’s α = 0.919). Although anxiety and depression were moderately-to-strongly correlated (r = 0.509, p < 0.01), only anxiety exhibited significant associations with diagnostic type (r = 0.201, p < 0.05) and treatment modality (r = 0.284, p < 0.01); multiple regression further identified anxiety as the sole significant predictor of treatment type (β = 0.239, p = 0.037), whereas depression showed no significant association (β = –0.040, p = 0.727). Additionally, female patients were significantly younger and had lower educational attainment, with education level positively correlated with insurance coverage (r = 0.263, p < 0.01), highlighting socioeconomic gradients in access to care. These findings establish the HADS as a valid and reliable instrument for screening psychological distress in Moroccan oncology patients and reveal a critical dissociation between anxiety and depression: anxiety emerges as a situational, treatment-sensitive marker responsive to therapeutic transitions, whereas depression appears more endogenous and independent of therapeutic modality. Consequently, the results support the implementation of differentiated, stepped-care psychosocial screening protocols that specifically target anxiety during treatment transitions, while underscoring the urgent need for equity-oriented policies addressing socioeconomic determinants of access to oncological care in resource-limited settings. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 953-962